Social and organizational learning in the adaptation to the process of climate change: The case of a Brazilian thermoplastic resins and petrochemical company. (20th July 2019) - Nicolletti, Mariana; Lutti, Natalia; Souza, Renato; Pagotto, Lívia
Abstract: Since climate change involves uncertainty, complexity and massive, rapid disruptions, companies seeking to adapt need to search for specific and non-traditional knowledge. Social learning approaches have emerged as a promising way to address the issue of adaptation to climate change. This paper examines the structuring of a business strategy for adaptation in a Brazilian thermoplastic resin and petrochemical company to exemplify the extent to which internal changes in the organization's understanding, norms and values derived from a social learning process. Hence, the main research question is "how are learning processes within a company—organizational learning—and social interaction in a Community of Practice—social learning—related and how do they contribute to leveraging changes in management practices in a company's adaptation to climate change? " The case study presents how the company's representatives' participation in a social learning process within a CoP supported not only the development of a comprehensive adaptation strategy but also the mainstreaming of climate concepts, impacts and adaptation actions. Therefore, it demonstrated that combining social learning and organization learning processes is useful to consistently build resilience, given that they are mutually supportive in the recognition of the relevance of adaptation, the dissemination of risk perception throughout the organization and the development of an internal capacity to continuously plan and act. Graphical abstract: Image 1 Highlights: Social learning set the floor for individual and organizational learning. The social learning process conferred legitimacy to the adaptation strategy. The company's organizational learning contributed to advancing group discussions. Sharing the company's learning strengthened group's cohesion and functionality. Learning at different levels promoted efficiency and innovation in management.